2012
DOI: 10.1007/s10014-011-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of primary bone xanthoma of the clivus

Abstract: Primary bone xanthoma is a rare type of tumor, and those developing primarily within the skull are even more unusual. In this case, a primary bone xanthoma of the clivus without endocrine or metabolic complications represents the first of this type to be reported. The patient, a 24-year-old woman, initially experienced frequent headaches. Subsequent skull tomography and bone-window computed tomography (CT) revealed a clearly demarcated osteolytic lesion in the clivus. T1-weighted magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It has been reported in the literature that intracranial xanthomas mostly occur in the temporal occipital region ( 4 ). The MR manifestations are mixed T1 and T2 signals, with flaky fat signal shadows, which are distinguished from diseases such as lipomas, cholesteatoma, and skull tumors ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that intracranial xanthomas mostly occur in the temporal occipital region ( 4 ). The MR manifestations are mixed T1 and T2 signals, with flaky fat signal shadows, which are distinguished from diseases such as lipomas, cholesteatoma, and skull tumors ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Though its etiology remains unclear, [14] a mild trauma may be a causative factor. [14,15] These are characterized by the presence of cholesterol deposits in the bone which occurs as a result of the leakage of lipid from the blood vessels at the site of the lesion which is then taken up by the macrophages. [10,16,17] Some authors consider xanthomatous lesions as neoplastic under the broad categoryof benign fibrous histiocytomas, while others favor a ''primary'' xanthoma of bone as a separate reactive entity.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors classify the xanthomas as: xanthomatous variant -when xanthomatous changes are found in preexisting bone lesions; secondary xanthoma -lesions associated with hyperlipidemia; and primary xanthoma -those not associated with hyperlipidemia 18,19 . Following the suggestion of these authors, the reported case could be considered a xanthomatous variant of simple bone cyst.…”
Section: Discussionmentioning
confidence: 99%